Study the possibilities of using Web 2.0 technologies to the development of intelligent educational resources - Alibiуev, D.B.; Seiуtimbetova, A.B. (Bulletin of the Karaganda University. Mathematics Series, 2015)
The article analyzes the problems of traditional educational programs arising in the preparation of professionals for the post-industrial economy. It is shown that many of these problems can be solved using the philosophy of Web 2.0. Studied Russian and foreign experience of using Web 2.0 tools to create innovative educational programs reviewed tools, services and Web 2.0 technologies in education. Considered the possibility of using philosophy and Web 2.0 technologies to the development of intelligent educational resources.